The effect of problem-based learning model based on earthquake disaster mitigation on critical thinking ability - Nazli, Syamsiatun; Nur , Muhammad Djamil M.; Rahmawaty , Rahmawaty (ARKA INSTITUTE, 2025)
This study aims to evaluate the impact of Problem-Based Learning (PBL) on the critical thinking skills of eighth-grade students at MTs Alkhairaat Pusat Palu, with a particular focus on earthquake disaster mitigation. This research is important because Indonesia, as a disaster-prone country, requires an effective educational approach to prepare students to face emergency situations, especially earthquakes. PBL can provide relevant and contextual learning experiences. This study used a quasi-experimental approach with unequal control groups. Participants included two classes; class VIII C which was the experimental class and received PBL intervention, while class VIII D served as the control class and received conventional instruction. Data were collected through essay tests administered before and after the intervention. Normality and homogeneity tests were conducted on the data before conducting a paired-sample t-test. The findings showed that students' critical thinking skills in the experimental class improved significantly, reaching a post-test average while the control class was lower. The t-test results indicated that PBL had a significant positive impact on critical thinking skills. Therefore, the PBL model aimed at disaster mitigation has proven effective in improving the development of critical thinking skills in students.